2019
DOI: 10.1002/jcp.28026
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 negatively modified osteosarcoma development through regulation of miR‐361‐5p and FoxM1

Abstract: This study was aimed to figure out whether long noncoding RNA MEG3/miR‐361‐5p/FoxM1 signaling would contribute to improved proliferation and metastasis of osteosarcoma cells. We altogether collected 204 pairs of osteosarcoma tissues and adjacent normal tissues, and obtained four human osteosarcoma cell lines. Then pcDNA3.1‐MEG3, si‐MEG3, miR‐361‐5p mimic, miR‐361‐5p inhibitor, pcDNA3.1‐FoxM1, si‐FoxM1, and negative control (NC) were, respectively, transfected into the osteosarcoma cells. Furthermore, real time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…For instance, lncRNA SBF2-AS1 mediated FOXM1 upregulation promotes cell proliferation in cervical cancer by sequestering miR-361-5p (26). LncRNA MEG3 obstructed osteosarcoma cell growth by modifying miR-361-5p and FoxM1 (27). Nevertheless, the molecular mechanism of miR-361-5p in BC are elusive.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lncRNA SBF2-AS1 mediated FOXM1 upregulation promotes cell proliferation in cervical cancer by sequestering miR-361-5p (26). LncRNA MEG3 obstructed osteosarcoma cell growth by modifying miR-361-5p and FoxM1 (27). Nevertheless, the molecular mechanism of miR-361-5p in BC are elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Sahin et al (43) showed that MEG3 attenuates proliferation and migration of OS cells through directly interacting with miR-664a. In addition, MEG3 can directly bind to miR-361-5p and increase its expression, downregulating the expression of FoxM1 (44). In this case, MEG3 abrogates development of OS via a miR-361-5p/FoxM1 axis instead of acting as a ceRNA.…”
Section: Roles Of Lncrna Meg3 In Bone Diseasesmentioning
confidence: 99%
“…Several of these lncRNAs are implicated in the downregulation of target gene expression (Yang et al, 2019), while others have been found to upregulate the expression of target genes (Li et al, 2013;Deng et al, 2019). An increasing number of studies indicate that lncRNAs play an important role in osteosarcoma development by affecting the following processes: cell proliferation, cellular invasion, migration, metastasis, stemness, fate, and EMT (Huang et al, 2018;Shen et al, 2019). Moreover, several lncRNAs are being actively investigated as prognostic markers for this disease (Chen et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism of interest, which has been reported on several times, involves lncRNAs working as competing endogenous RNAs (ceRNA), in which the lncRNA can act as a sponge for specific miRNAs and indirectly regulate the expression of tumorrelated genes Deng et al, 2019;Shen et al, 2019). Tp53, a well-known and extensively studied gene in tumors, was first reported to exhibit intron 1 rearrangement (Masuda et al, 1987).…”
Section: Introductionmentioning
confidence: 99%